The Biopsychosocial Model and Perinatal Health Care: Determinants of Perinatal Care in a Community Sample - Duberstein, Zoe T.; Brunner, Jessica; Panisch, Lisa S.; Bandyopadhyay, Sanjukta; Irvine, Carrie; Macri, Jenna A.; Pressman, Eva; Thornburg, Loralei L.; Poleshuck, Ellen; Bell, Keisha; Best, Meghan; Barrett, Emily; et al. (Frontiers in Psychiatry, 2021)
Insufficient care during pregnancy is associated with poorer maternal health, lower birth weight, higher rates of prematurity, and infant mortality. The current literature on perinatal care utilization provides the most support for sociodemographic factors as predictors of inadequate care, but an explanation of the underlying causes for this association is lacking. Applications of the biopsychosocial model’s focus on psychosocial and cultural contexts may provide clues to improving perinatal health care and particularly health inequalities. We propose a specific application of the biopsychosocial model to perinatal health that conceptualizes prenatal and postpartum clinic attendance as health markers that are influenced by psychological factors and family and social context. Clinic attendance data were abstracted from the electronic medical records of N = 291 participants enrolled in a longitudinal pregnancy cohort study of healthy women who have been followed since the first trimester; detailed prenatal psychological, social, and sociodemographic data were collected from self-report questionnaire and interview. Bivariate analyses indicated socio-demographic (e.g., race), psychological (e.g., response to perceived racism, affective symptoms, trauma experience), and social and family context (e.g., social support, family size) significantly influenced pre- and post-natal care utilization. Multivariate logistic regression analyses, adjusting for medical complications, identified social and family context as robust predictors of perinatal care utilization. The findings underscore the need for biopsychosocial models of health care and highlight several potential strategies for improving health care utilization.